Joseph Dewey Soper, 1893-1982 - Soper, Roland; Beck, Tom (ARCTIC, 1983)
. "Dewey Soper is a man of action and acuity, in a particular sense l'homme engagé, second to none as a pioneer of the North whose courage, industry and initiative inspire us to find our country and extend all its benefits into our lives." Those well-chosen words stand today as an epitaphic tribute to a man who spent the early years of his career in arctic exploration and a lifetime in the study of natural history and in pursuit of scientific knowledge. . - he was an outdoorsman first and his vocations and avocations stemmed from this prerequisite. . In the context of his lifespan, arctic explorations occupied a small segment of his 89 years, yet they left an indelible imprint on his life and in his own mind forever stood as the pinnacle of his achievements. His three expeditions were conducted in 1923, 1924-26 and 1928-31. The latter two took him to southern Baffin Island and comprised eleven separate journeys of exploration. . Viewed in perspective - considering the lack of modern equipment and the unsophisticated means of communication and travel - those ventures into the interior and across Baffin Island were remarkable conquests. . Soper's successful crossing and return in January-February, 1926, covered 1050 kilometres. His courage and determination are reflected in two sentences from his own writings: "I still feel extraordinary admiration for the splendid efforts of Akatuga and Newkequak who endured so much fatigue and suffering without a murmur, and what seemed the incredible hardship for the dogs. It is impossible to forget the frightful cold of 70° below zero as we forged our way over the frozen Lake Nettilling and across the Great Plain of the Koukdjuak to Foxe Basin and back to the east coast." In 1929, newspapers published accounts of J.D. Soper and his successful six-year, 30 000-mile search for the nesting grounds of the blue goose. . The location of the nesting grounds of the blue goose had been a mystery to naturalists. In 1926 he met an Inuk hunter on the Tikkuut Islands .who claimed that he ...